Pengaruh Hedonic Shopping Motivation, Shopping Lifestyle Dan Self Control Terhadap Impulse Buying Pada Pengguna E-Commerce Tokopedia Di Denpasar - Novyantari, Ni Putu Widya; Imbayani, I Gusti Ayu; Prayoga, I Made Surya (Jurnal Maneksi (Management Ekonomi Dan Akuntansi), 2024)
This study aims to examine and obtain empirical evidence on the influence of hedonic shopping motivation, shopping lifestyle, and self-control on impulse buying among Tokopedia e-commerce users in Denpasar. This research employs a non-probability sampling method using a purposive sampling approach. The population consists of Tokopedia e-commerce users who engage in impulsive purchases, which are not precisely known, and the sample size is determined based on the number of indicators in the model, ranging from 5 to 10. The study includes 16 items as indicators, thus the sample size is determined to be 16 x 7 = 112 respondents. Path analysis is utilized to test hypotheses using SPSS version 25. The research findings indicate that hedonic shopping motivation and shopping lifestyle have a positive and significant impact on impulse buying, while self-control significantly negatively influences impulse buying among Tokopedia e-commerce users in Denpasar.